2022
DOI: 10.1002/jctb.7218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment on the structural, thermal, and mechanical properties of sugarcane bagasse as filler for starch‐based bioplastic

Abstract: BACKGROUND:The demand for green products is pushing industries to search for more eco-friendly materials, especially for food packaging applications. Starch biopolymer has been recognized as biodegradable material that can be produced from various plants. However, the strength of starch-based bioplastic retards their widespread application. Simultaneously, the high amount of agricultural waste produced by the food industry has been a growing environmental issue. Incorporating agro-waste fibers as a biofiller i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For both blends, the slope of this portion of the curve becomes more gradual as the proportion of RF waste increases. The contaminants or dust that occasionally make their way into mixtures while manufacturing flexible plastics could be the cause [28]. The variations in weight loss and decomposition rates proved that additional substances impacted plastic decomposition was agreed by Majder-Lopatka et al, [29].…”
Section: Thermal Propertiesmentioning
confidence: 74%
“…For both blends, the slope of this portion of the curve becomes more gradual as the proportion of RF waste increases. The contaminants or dust that occasionally make their way into mixtures while manufacturing flexible plastics could be the cause [28]. The variations in weight loss and decomposition rates proved that additional substances impacted plastic decomposition was agreed by Majder-Lopatka et al, [29].…”
Section: Thermal Propertiesmentioning
confidence: 74%
“…Hamin et al. 46 showed that the thermal stability was enhanced significantly with the incorporation of SCB into the biopolymer. Mulinari et al.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal properties of the fabricated composite were increased through the treatment with MAPP. Hamin et al 46 showed that the thermal stability was enhanced significantly with the incorporation of SCB into the biopolymer. Mulinari et al 47 showed that modified fiber-reinforced polymeric matrix composites of HDPE presented higher thermal stability than the non-modified composites.…”
Section: Tgamentioning
confidence: 99%
“…In contrast, the amount of food wasted is influenced by societal factors as well as the attitudes and habits of each individual. 7 Plastic pollution and food waste are the two major common issues that the world is facing nowadays. However, in a vain attempt to solve the food waste problem, another issue has been made worse by the arrival of plastic containers as a simple and practical solution to enhance food preservation and minimise the probability of producing waste.…”
Section: Introductionmentioning
confidence: 99%